Programas do Chacrinha: inovação da linguagem televisual - Rohrer, Cleber Vanderlei (2010)
On this research the artistic trajetory of the presenting Aberlardo Barbosa, also known as Chacrinha, is presented, from the beginning of his career on the radio until he entered his ideal vehicle as a communicator: the television. The presenting is considered by many televisual language criticals as one of the most polemicals and outstanding characters from this set. Chacrinha s importance for the brasilian television is due to his irreverence, criativity and also due to some of his unconventional behavior (anarchic ones) that made him different from the other ones acting at that time. Aberlardo Barbosa s career starts on the radio in the fourties bunching all the popular scenary as cassinos, circus and popular parties, which are a couple of activities that influenced him until his arrival on the TV. Once on the TV his trajetory throghout the TV stations, mainly Tupi TV, Globo TV, and Bandeirantes TV is introduced lightning up his resources to capture the audience, including the tenderfoot performances, his own performing dancers, who were known as chacretes, a description of his audience and some problems he has had with the censorship. The theorical references concentrates on authors as Décio Pignatari who has analysed different TV programs in the late senventies, among them the Chacrinha s ones, and Arlindo Machado who has presented a thesis about the tv and a detaled anlyses made yet in the beggining of the seventies when Muniz Sodré does a critical observation about the brasilian culture and the communication vehicles. Chacrinha aesthetics and his televisual language are approached in a very specific way in which it is introduced as a spilling from other means of communication that have influenced him and made him become a unique presenting, besides the fact that he has been an icon for tropicalism. In order to head into an end it is outstanded that it might be a legacy left by Chacrinha in our television, and his importance in this set has been kept on even after his very last show